Urothelial Papilloma of the Urinary Bladder in Children: Report of Two Cases - Kata Davidovics; Sandor Davidovics; Andras Farkas; Noemi Benedek; Tamas Tornoczki; Daniel Kardos; Anna Davidovics; Peter Vajda (Georg Thieme Verlag KG, 2020)
Urothelial neoplasms of the bladder (UNB) are considerably rare throughout the pediatric population. UNB develops from the urothelial tissue in the form of a benign disease, generally favoring a successful prognosis in the majority of cases. The authors present the diagnosis and treatment regarding two medical case reports in which urothelial papilloma was diagnosed and effectively treated. Case 1: A 15-year-old male patient was presented to our clinic complaining of a painless yet distinctive, macroscopic form of hematuria. Following a routine examination, which included ultrasound (US) and intravenous pyelography, the urethrocystoscopy revealed an intravesical solitary lesion positioned in the vicinity of the left ureteral orifice. Additionally, histology confirmed urothelial papilloma. During the follow-up, laboratory, urinary control tests, and US results all proved negative. Case 2: A 13-year-old male patient was admitted to our clinic and examined, in regard to complaints associated with recurrent abdominal pain. The pathology was discovered incidentally on abdominal US. Preoperative US and magnetic resonance imaging (MRI) studies ensued, resulting in a scheduled MRI, followed by urethrocystoscopy, which confirmed an intravesical solitary lesion positioned near the right ureteral orifice. Histology revealed urothelial papilloma. During the follow-up control cystoscopy, one resection was repeated due to the presence of a residual tumor. Today, 10 years since the presence of uroepithelial papilloma, both patients are asymptomatic and tumor-free. If there is likely suspicion of recurrence, cystoscopy is recommended.